Transformation of print media in the digital era: media convergence of Kedaulatan Rakyat - Qholiva Yuni Fadilla; Filosa Gita Sukmono (International Journal of Communication and Society, 2021)
In Indonesia, mainstream media industries are facing numerous challenges in applying media convergence, including the media that has been established for years, such as Tempo and Pikiran Rakyat, which have experienced the hurdles and even failure in adopting media convergence. Meanwhile, Kedaulatan Rakyat, as the oldest local print media company in Indonesia, also converged and transformed its institution through media multiplatform diversification to answer the challenge of industry 4,0. The research aimed to interpret and describe the media converge conducted by Kedaulatan Rakyat. The research method used was case-study and with in-depth interviews, observation, and documentation as the data collection. The research found that Kedaulatan Rakyat tried to answer the development of technology by adopting media convergence. The convergence applied was newsroom 3.0 or integrated newsroom. However, Kedaulatan Rakyat exercised an inaccurate strategy in executing its newsroom convergence 3.0, namely by preserving conservative traditions. After abandoning newsroom convergence, Kedaulatan Rakyat performed content-sharing activity and deep and shallow strategy. However, couple with the landscape of journalism of Kedaulatan Rakyat that had not met the criteria of multi-tasking and inequality and role distribution among media, the new activities also did work optimally. In light of that, the preservation of conservation traditions in media companies should be considered as a bar of media convergence adoption.